2004
DOI: 10.5194/hess-8-742-2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative simulation of the nitrogen dynamics using the INCA model and a neural network analysis: implications for improved nitrogen modelling

Abstract: Continuing deposition of nitrogen in forested catchments affects stream and groundwater quality. However, the dependence of nitrogen dynamics on climatic and hydrological boundary conditions is still poorly understood. These dynamics have been investigated by applying the process-oriented Integrated Nitrogen in CAtchments (INCA) model and an artificial neural network to the data set from the forested Steinkreuz catchment in South Germany. The data comprise daily values of precipitation, air temperature and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Process-based models can identify mechanisms but care must be taken in their application to ensure all relevant processes are represented (Futter and de Wit, 2007). Comparisons of ANN and processbased model simulations have been published before (Lischeid and Langusch, 2004). However, they may not have adequately calibrated the process-based model.…”
Section: Comparison Of With Artificial Neural Networkmentioning
confidence: 99%
“…Process-based models can identify mechanisms but care must be taken in their application to ensure all relevant processes are represented (Futter and de Wit, 2007). Comparisons of ANN and processbased model simulations have been published before (Lischeid and Langusch, 2004). However, they may not have adequately calibrated the process-based model.…”
Section: Comparison Of With Artificial Neural Networkmentioning
confidence: 99%
“…The analysis by Creed et al (1996) showed a highly scattered relationship between soil saturation deficit and nitrate-N concentration with an unexpected co-occurrence of high saturation deficit and high nitrate-N concentration during late summer and early autumn. The seasonal variability might be an important factor since the neural network analysis by Lischeid and Langusch (2004) identified mean daily temperature as an important driving variable for modelling streamflow nitrate concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Processbased models can identify mechanisms but care must be taken in their application to ensure all relevant processes are represented (Futter and de Wit, 2008). Comparisons of ANN and process-based model simulations have been published before (Lischeid and Langusch, 2004). However, they may not have adequately calibrated the process-based model.…”
Section: Comparison With Artificial Neural Networkmentioning
confidence: 99%